KONSEP DIRI WANITA MODEL FASHION SHOW DI PEKANBARU - Azhar, Stefy Adelia; Wirman, Welly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
A woman's life fashion show models synonymous with glamorous lifestyle, nightlife, and even sex. In order to meet the demands and lifestyle as a model, they often do things - negative things like, into prostitution